Reversion of a human immunodeficiency virus type 1 integrase mutant at a second site restores enzyme function and virus infectivity. - Taddeo, B (1996)
The integration of a DNA copy of the retroviral RNA genome into the host cell genome is essential for viral replication. The virion-associated integrase protein, encoded by the 3' end of the viral pol gene, is required for integration. Stable virus-producing T-cell lines were established for replication-defective human immunodeficiency virus type 1 carrying single amino acid substitutions at conserved residues in the catalytic domain of integrase. Phenotypically reverted virus was detected 12 weeks after transfection with the integrase mutant carrying the P-109-->S mutation (P109S). Unlike the defective P109S virus, the revertant virus (designated P109SR) grew in CD4+ SupT1 cells. In addition to the Ser substitution at Pro-109, P109SR had a second substitution of Ala for Thr at position 125 in integrase. Site-directed mutagenesis was used to show that the P109S T125A genotype was responsible for the P109SR replication phenotype. The T125A substitution also rescued the in vitro enzyme activities of recombinant P109S integrase protein. P109S integrase did not display detectable 3' processing or DNA strand transfer activity, although 5 to 10% of wild-type disintegration activity was detected. P109S T125A integrase displayed nearly wild-type levels of 3' processing, DNA strand transfer, and disintegration activities, confirming that T125A is a second-site intragenic suppressor of P109S. P109S integrase ran as a large aggregate on a size exclusion column, whereas wild-type integrase ran as a monomer and P109S T125A integrase ran as a mixed population. Pro-109 and Thr-125 are not immediately adjacent in the crystal structure of the integrase catalytic domain. We suggest that the T125A substitution restores integrase function by stabilizing a structural alteration(s) induced by the P109S mutation.